Non-Muslim Chinese in Malaysia: a current state of Islamic daʿwah (Preaching) to non-Muslim Chinese in the state of Kelantan - Muhamad Shukri, Abdul Salam (IIUM Press, International Islamic University Malaysia, 2023)
This article aims at discussing a current state of Islamic Da‘wah (preaching) to non-Muslim Chinese in the state of Kelantan. As predominately a Malay state, Kelantan hosts a small number of Chinese populations. However, a survey reveals that it is only 3% of Kelantan Chinese has embraced Islam compared to the total number of Kelantan Chinese of 49,067 people up until 2002. This study employs qualitative methodology in which the data collected are analyzed using textual and content analysis approach. Looking at the current state of Islamic Da‘wah this review has identified various issues and challenges in preaching to the non-Muslim Chinese community in Kelantan. Among the obstacles of accepting Islam are prejudices, misunderstandings, bad images of Islam as well as a lot of confusion in understanding Islam and Malay society. Thus, more current studies needed in order to gauge this trend in non-Muslim Kelantanese Chinese community.